2018
DOI: 10.1093/ofid/ofy243
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Brain Impact of Aging and HIV Severity in Chronic HIV Using Multiparametric MR Imaging and MR Spectroscopy

Abstract: BackgroundCombination antiretroviral therapy (cART) has transformed HIV into a manageable but complex chronic disease, in which it is uncertain which brain insults may relate to age vs initial disease severity. We evaluate N-acetyl-aspartate/creatine (NAA/Cr), white matter hyperintensities (WMH), and mean cortical thickness to identify which subclinical markers of brain insult best relate to CD4 nadir and aging. This is a prospective study of the association between brain markers with age and initial infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…19 This is consistent with the positive association between NAA levels and CD4 nadir in chronic PWH who are on cART and have largely successful viral suppression. 30-32 Second, progressive or transient neuronal/axonal injury may contribute to additional NAA reduction, including ongoing neuroinflammation (such as correlations with CSF/plasma inflammation markers 13,33 ), current immunosuppression, 34 viral load, 35 and common comorbidities in PWH (e.g., substance abuse). 35 Progressive decline in NAA concentrations is also evident in longitudinal HIV studies with human 36 and nonhuman subjects.…”
Section: Discussionmentioning
confidence: 99%
“…19 This is consistent with the positive association between NAA levels and CD4 nadir in chronic PWH who are on cART and have largely successful viral suppression. 30-32 Second, progressive or transient neuronal/axonal injury may contribute to additional NAA reduction, including ongoing neuroinflammation (such as correlations with CSF/plasma inflammation markers 13,33 ), current immunosuppression, 34 viral load, 35 and common comorbidities in PWH (e.g., substance abuse). 35 Progressive decline in NAA concentrations is also evident in longitudinal HIV studies with human 36 and nonhuman subjects.…”
Section: Discussionmentioning
confidence: 99%
“…With the successful treatment of combination antiretroviral therapy (cART), human immune deficiency virus (HIV) associated neurocognitive disorders has become the major concern for HIV infected patients (Heaton et al, 2010) and caused a series of neurocognitive deficits such as memory, language impairments that seriously affect the quality of daily living for HIV patients (Saylor et al, 2016). Several studies have reported people living with HIV are at high risk of age‐related comorbidities (Kooij et al, 2016; Schouten et al, 2014) and displayed accelerated brain aging (Kim‐Chang et al, 2019; Kuhn et al, 2018) even in viral suppression, which indicated the influences of HIV on the aging process in human brain (Chu et al, 2018; Hakkers et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although we found an increase in Cho/Cr ratio, we did not find any changes in NAA/Cr and MI/Cr ratios, which might be related to a difference in the inclusion criteria. Other studies have included patients with detectable viral load, CD4+ T lymphocytes < 200 cells/µL ( 9 , 12 ) , and dementia ( 9 - 13 , 17 ) or did not analyze all major peaks in the spectroscopy curve ( 14 - 18 ) , whereas in this study, all patients had undetectable viral load and only had memory deficits. Moreover, the small sample size of this study may have contributed to the absence of differences in the other metabolic ratios.…”
Section: Discussionmentioning
confidence: 96%
“…H-MRS has also been studied in HIV-positive patients, generally showing a decreased NAA/Cr ratio and increased Cho/Cr and MI/Cr ratios in several brain regions, including the medial temporal lobe, frontal lobe, and posterior cingulate gyrus (9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . However, with regard to the limbic system in the case of clinically significant memory deficits, posterior cingulate gyrus H-MRS quality is superior than medial temporal lobe H-MRS, due to the close proximity of the latter to the skull base causing susceptibility artifacts.…”
Section: Introductionmentioning
confidence: 99%